2017
DOI: 10.1016/j.jad.2017.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Neural reactivity to reward and internalizing symptom dimensions

Abstract: Background Reduced reward responsiveness, measured via the event-related potential (ERP) component the reward positivity (RewP), has been linked to several internalizing psychopathologies (IPs). Specifically, prior studies suggest that a reduced RewP is robustly related to depression and to a lesser extent anxiety. No studies to date, however, have examined the relation between the RewP and IP symptom dimensions in a heterogeneous, clinically representative patient population that includes both depressed and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
22
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 48 publications
5
22
2
1
Order By: Relevance
“…Consequently, the large variability in the electrophysiological results across studies on feedback processing in GAD, MDD and OCD does not allow to advance conclusions on whether internalization reduces the processing of external signals. Moreover, in a recent study, Burkhouse and collaborators [32] found that feedback processing in internalizing psychopathologies might differ according to the level of distress/misery or fear symptoms [1]. In fact, abnormal feedback processing seems to be linked to the severity of distress/misery but not to fear symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the large variability in the electrophysiological results across studies on feedback processing in GAD, MDD and OCD does not allow to advance conclusions on whether internalization reduces the processing of external signals. Moreover, in a recent study, Burkhouse and collaborators [32] found that feedback processing in internalizing psychopathologies might differ according to the level of distress/misery or fear symptoms [1]. In fact, abnormal feedback processing seems to be linked to the severity of distress/misery but not to fear symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…21 Reward processing is often impaired in late life depression. [22][23][24] Decreased reward responsiveness has been associated with depressive symptoms [25][26][27][28] and is correlated with severity of anhedonia. 29 Most neurobiological studies of reward processing have primarily investigated responses to monetary outcomes (i.e.…”
mentioning
confidence: 99%
“…A number of studies have examined the RewP, an ERP component elicited by feedback indicating rewards versus losses, that is thought to reflect activity of the reward circuit (i.e., the ventral striatum, caudate and dACC) (29)(30)(31). Depressed adults show decreased RewPs (32,33) and increased depression in children/ adolescents is related to reduced RewP (26,34,35). A reduced RewP predicts later depression in adolescents (25,34) and is related to the severity of anhedonia in adults (36).…”
mentioning
confidence: 99%